Contribution of career counseling, internship experience and advisor toward students work readiness at vocational high school - Rahmadani, Kurniati; Irfan, Dedy (Universitas Negeri Padang, 2021)
The problems in this study are 1) The lack of subject relevance at schools with its implementation in the industrial world, 2) DU / DI instructors only guide what needs to be done in the field, without giving direct guidance, 3) Inadequate career guidance received by students at school. Students only get a little information related to the expertise program they choose, 4) The advisor is only limited to monitoring students in the Internship, without providing optimal reinforcement and direction to students. This study aims to: 1) Contribute as career guidance to student work readiness at SMKN 2 Padang, 2) Know the contribution of internship experience with student work readiness at SMKN 2 Padang, 3) Understand the contribution of the mentoring teacher to student work readiness at SMKN 2 Padang, 4) Knowing the contribution of internship career guidance and advisors together with the student work readiness at SMKN 2 Padang. This type of research is quantitative using correlational research methods. This research was conducted at SMK Negeri 2 Padang. The population of this study were students of grade 12 at SMKN 2 Padang. The sampling technique was proportional random sampling, with a total sample of 83 students. The data analysis technique used is quantitative data analysis techniques. Based on the research results, it was found that the data were normal, and linear and did not occur in multicollinearity. The results of the research are: 1) There is a contribution of career guidance to student work readiness at SMK N 2 Padang, 2) There is a contribution of internship experience to student work readiness at SMKN 2 Padang, 3) There is a contribution of an advisor to student work readiness at SMK N 2 Padang, 4) Career Guidance Internship Experiences and advisors together provide a positive relationship to student work readiness at SMK N 2 PADANG by 78.0%.